Biodegradation of PVP-CMC hydrogel film: a useful food packaging material - Roy, Niladri; Saha, Nabanita; Kitano, Takeshi; Saha, Petr (Carbohydrate polymers, 2012)
Hydrogels can offer new opportunities for the design of efficient packaging materials with desirable properties (i.e. durability, biodegradability and mechanical strength). It is a promising and emerging concept, as most of the biopolymer based hydrogels are supposed to be biodegradable, they can be considered as alternative eco-friendly packaging materials. This article reports about synthetic (polyvinylpyrrolidone (PVP)) and biopolymer (carboxymethyl cellulose (CMC)) based a novel hydrogel film and its nature of biodegradability under controlled environmental condition. The dry hydrogel films were prepared by solution casting method and designated as 'PVP-CMC hydrogel films'. The hydrogel film containing PVP and CMC in a ratio of 20:80 shows best mechanical properties among all the test samples (i.e. 10:90, 20:80, 50:50, 80:20 and 90:10). Thus, PVP-CMC hydrogel film of 20:80 was considered as a useful food packaging material and further experiments were carried out with this particular hydrogel film. Biodegradation of the PVP-CMC hydrogel films were studied in liquid state (Czapec-Dox liquid medium+soil extracts) until 8 weeks. Variation in mechanical, viscoelastic properties and weight loss of the hydrogel films with time provide the direct evidence of biodegradation of the hydrogels. About 38% weight loss was observed within 8 weeks. FTIR spectra of the hydrogel films (before and after biodegradation) show shifts of the peaks and also change in the peak intensities, which refer to the physico-chemical change in the hydrogel structure and SEM views of the hydrogels show how internal structure of the PVP-CMC film changes in the course of biodegradation.
Keywords: Povidone; Hydrogels; obaly potravin; sodná sůl karboxymethylcelulosy; pevnost v tahu; viskozita; Elasticity; pružnost; půda; Soil; Viscosity; Tensile Strength; Carboxymethylcellulose Sodium; Food Packaging; Biodegradation, Environmental; biodegradace; povidon; hydrogely